A Structural Model of Prospective Science Teachers' Nature of Science Views - BAYRAM, HALE (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2010)
This study aims to establish a viable structural model of prospective science teachers' nature of science (NOS) views, which could be used as an analytical tool for understanding the complex relationships between prospective teachers' conceptions of NOS and factors possibly affecting their conceptions. In order to construct such a model, likely factors that might influence prospective teachers' NOS views were hypothesized. These included science process skills; attitudes toward science teaching; academic achievement in pedagogical and science courses; and social, religious, economic, political, aesthetic, and theoretical values. The hypothetical model was then developed and modified using structural equation modeling methodology. The final viable model indicates that attitudes toward science teaching, science process skills, academic achievement in pedagogical courses, religious values, and economic values explain NOS views with low predictive power.
Keywords: nature of science; prospective teachers; model; PRESERVICE SCIENCE; CONCEPTUAL CHANGE; STUDENTS; INSTRUCTION; BELIEFS; KNOWLEDGE; EXPLICIT; ATTITUDES; INQUIRY; GRADERS